tdkp/AQUA: Unified modelling of electroluminescence in nanostructures - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (9th International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD 2009, 2009)
This article summarizes the capabilities of the optoelectronic simulation framework tdkp/AQUA aimed at the description of electroluminescence in semiconductor nanostructures such as light-emitting diodes (LEDs). tdkp is a standalone finite-element software able to accurately calculate strain, built-in fields due to spontaneous and piezoelectric polarization, quantum states, gain and luminescence spectra in zero- to three-dimensional structures. AQUA calculates transport through nanostructures using an original model which accounts for the distinct behaviour of carriers confined to active regions and unconfined carriers. Furthermore, it computes electroluminescence spectra via a self-consistent coupling of the confined carriers to quantum-mechanical calculations using tdkp. Two examples are presented which highlight the versatility and generality of the developed simulator. ©2009 IEEE.
CRIS-Team Scopus Importer:2021-06-11